Taking Root: The Establishment and Development of the College of Agriculture at Fujian Union University in the Early Years of the War of Resistance - CUI Junwei, (Journal of Research for Christianity in China (JRCC), 2025)
In the early years of the War of Resistance, the faculty and students of the College of Agriculture at Fujian Union University closely tied their own destiny to that of the nation, achieving remarkable educational accomplishments under arduous conditions. The college not only expanded its educational scope, cultivating numerous specialized agricultural professionals for society, but also emphasized practical engagement with local development and construction. This approach transformed the pre-war perception of higher education as detached from the populace and elitist. The faculty and students of Fujian Union University's College of Agriculture made significant contributions to the continuity and advancement of higher education in Fujian during the early years of the War of Resistance.
Keywords: War of Resistance Against Japan, Peking Union Medical College, Christian Education